Development of project-based student worksheets on renewable energy by utilising rubber fruit shell waste to increase motivation - Dwita Kartika Sari; Hamdi Akhsan (Universitas Sriwijaya, 2025)
The learning activities are impacted by the switch from the 2013 curriculum to the Merdeka curriculum. Students become the focal points of learning and outcome-based learning in an autonomous curriculum. Additionally, the students had the chance to work on the project in person. This project aims to use rubber shell waste to create PjBL-based student worksheets for high school students that are relevant and useful on issues related to renewable energy. The Borg and Gall development model, which has seven stages, was used in this investigation. A Prabumulih student who was an X-man was the focus of his investigation. Results of validation from a variety of factors, including technical requirements of 83.3% with extremely valid category and component features of student worksheet 90% with very valid category, 86.7% of the construction conditions have very valid categories, 71.7% of the didactic requirements have valid categories, and 86.7% of the very valid categories have student worksheet compatibility with PjBL syntax. In the field test, the extremely practical scored 90.67 per cent, while in the limited test, the practicality result was 88.2 per cent for the useful category.